Determinants of the Distance between Sovereign Credit Ratings and Sub-Sovereign Bond Ratings : Evidence from Emerging Markets and Developing Economies - Mohapatra, Sanket; Nose, Manabu; Ratha, Dilip (Taylor and Francis, 2018)
This article explores factors that affect the distance between sovereign credit ratings and the ratings assigned to new foreign-currency bonds issued by sub-sovereign entities (such as private non-financial corporations, financial firms, and public sector enterprises) in 47 emerging markets and developing economies. Censored and double-hurdle regression models are used to estimate the relative contributions of bond-level, issuer-level, and macroeconomic factors that determine this distance, separately for those rated at or below the sovereign rating and those rated above. For the three quarters or more of sub-sovereign bond ratings that are constrained by the sovereign rating ceiling, a Tobit regression model shows a smaller distance – suggesting stronger sovereign–corporate linkages – for public sector enterprises and financial firms relative to other firms. Riskier global financial conditions are also associated with sub-sovereign bonds being rated closer to the sovereign rating. For the small number of sub-sovereign bonds rated higher than the sovereign rating, a double-hurdle model shows that certain debt features – such as bonds backed by future-flow receivables or other collateral or structured as Special Purpose Vehicles (SPV) – significantly raise the likelihood of piercing the sovereign rating ceiling and also increase the distance above the sovereign ceiling.